Determining torque and angulation of permanent teeth in cases of brachygnatic dental arches depending on dentition type - E. G. Vedeshina; D. A. Domenyuk; S. V. Dmitrienko (Кубанский научный медицинский вестник, 2015)
The work highlights the results of a study performed involving 257 patients of both sexes in the first period of their adulthood, who had physiological occlusion of permanent teeth and brachygnathic shape of dental arches. Dental arches are considered brachygnath^ in cases where the width prevails largely over the depth, which makes the arch appear as short and wide. For cases with brachygnathic normodontia and microdontia the angles of vestibular-lingual inclination matched the low torque braces. Brachygnathic macrodontia arch shape showed the angles of vestibular-lingual inclination closer to the standard torque. The angulation angles in cases with brachygnathic shape of dental arches proved to be of no dependence with the size of the permanent teeth, while the difference in such factors was not significant.